A note on History of Rome school of TMM - Ceccarelli, Marco (Anales de Ingeniería Mecánica, 2025)
In this paper a historical survey is presented on distinguished figures and activities evolution in the fields of TMM (today MMS) within the academic frames of the school of engineering in Rome. As in many other Italian University, the modern academic tradition of the University of Rome started since the Renaissance time and the specific activity on Mechanical Engineering was officially established and well developed in 19th century. The background from an early University in Rome is remembered as a base for the well-focused interests in TMM during the 19th century with significant results by distinguished figures. The early modern historical developments are outlined as starting in the second half of 19 the century referring to Carlo Saviotti, Lorenzo Allievi, Anastasio Anastasi, and later to Manlio Oberziner, Arnaldo Castagna, and Giovanni Scotto Lavina. Many others also contributed significantly and their achievements are reported in the historical account, like for example Adalberto Vinciguerra who, with his international views and activities, was the first to be well involved in the International Federation IFToMM: In more recent times the Rome school proliferated following the establishment of the second University of Rome in Tor Vergata in early 1980s and later the third University of Rome near Viale Marcon in the early 2000s. Short account is discussed to give a panorama of the different groups in the three universities that very soon developed their own community with a differentiated identity and activities. It is possible to recognize a two generations of figures who do not developed their activity in the origin La Sapienza University of Rome.The paper gives an account of a cultural heritage in TMM and MMS Rome school frames in TMM/MMS by reporting information on main distinguished figures of teachers-investigators and their achievements with contribution to the development of mechanical engineering and specifically TMM or MMS with values of national and international interests. A goal of the paper is also to refresh consideration of the past looking at technical contents for more technical-historical investigations that can be useful to keep memory of past mentors, but to track local evolutions like the one of the Rome school of TMM-MMS as awareness source of future trends